BcSUN1, a B. cinerea SUN-Family Protein, Is Involved in Virulence - Pérez-Hernández, Alicia; González, Mario; González, Celedonio; van Kan, Jan A. L.; Brito, Nélida (Frontiers in Microbiology, 2017)
BcSUN1 is a glycoprotein secreted by Botrytis cinerea, an important plant pathogen that causes severe losses in agriculture worldwide. In this work, the role of BcSUN1 in different aspects of the B. cinerea biology was studied by phenotypic analysis of Bcsun1 knockout strains. We identified BcSUN1 as the only member of the Group-I SUN family of proteins encoded in the B. cinerea genome, which is expressed both in axenic culture and during infection. BcSUN1 is also weakly attached to the cellular surface and is involved in maintaining the structure of the cell wall and/or the extracellular matrix. Disruption of the Bcsun1 gene produces different cell surface alterations affecting the production of reproductive structures and adhesion to plant surface, therefore reducing B. cinerea virulence. BcSUN1 is the first member of the SUN family reported to be involved in the pathogenesis of a filamentous fungus.